Sabbath Keeping as Metaphor in the "Gospel of Thomas" - King, Joshua 1979- (2019)
In this article, I explore the current state of the question concerning the meaning of the phrase σαββατίσητε τὸ σάββατον in logion 27 of the Gospel of Thomas. How one translates this phrase is in large part determined by what one views Thomas's theological outlook to be. Thus, Tjitze Baarda, who believes that Thomas is Gnostic, argues that the phrase means "to abstain from Yaldabaoth," while April DeConick, who believes that Thomas comes from Jewish Christian mysticism, argues that the phrase is a literal admonition to observe the Sabbath. Based on lexical and contextual considerations, I argue, with Simon Gathercole, that the logion most likely does not encourage literal Sabbath observance but instead that Sabbath keeping serves as a metaphor for general abstinence from evil. This squares well with what is found in other contemporaneous documents, including the works of Justin Martyr, Irenaeus, Tertullian, and Ptolemy the Gnostic.
Keywords: Biblical Commentaries; BIBLICAL teaching on the Sabbath; Christian Mysticism; Gnostic literature; Gospel of Thomas (Coptic Gospel); Gospel of Thomas; Jewish practice; Sabbath; Fasting